Money and Heritage: An Ontological Analysis a 10,000 Banknote from the 2005 Issue - Sawalika, Fella Mawaddah; Fatimah, Siti; Anwar, Syafri (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2026)
The Limas House at the Balaputra Dewa Museum is a cultural heritage site that must be preserved. The Limas House has been a typical Palembang traditional house since 1930. The first owner of the Limas House was Syarif Abdurachman Alhabsi, who later purchased it from the Palembang City Government. This Limas House is divided into two parts facing opposite directions. The owner of the rear house is Syarif Ali. The characteristic of the four-story Limas House building is called Bengkilas. At major events, seating positions depend on family status. In 1995, Queen Beatrix of the Netherlands visited the Balaputra Dewa Museum. The Limas House was legalized as an icon on the 2005 Rp. 10,000 banknote, along with an image of the South Sumatran hero, Sultan Mahmud Badaruddin II. Since the 2005 Rp. 10,000 banknote was issued, the number of national tourists visiting Palembang and the Balaputra Dewa Museum has increased. Students and schools in Palembang have involved the Balaputra Dewa Museum in learning about Local Wisdom and contributing to school activities. Each structure in the Balaputra Dewa Museum holds meaning and value for the people of Palembang. This research aims to raise awareness among the people of Palembang and the younger generation of the city about the need to increase their knowledge of Limas Houses and promote traditional tourism. The researchers used interviews with tour guides and secondary data from a literature review.